Distinguishing PTSD, complex PTSD, and borderline personality disorder using exploratory structural equation modeling in a trauma-exposed urban sample. (May 2022) - Powers, Abigail; Petri, Jessica M.; Sleep, Chelsea; Mekawi, Yara; Lathan, Emma C.; Shebuski, Karen; Bradley, Bekh; Fani, Negar
Abstract: There is debate about the validity of the complex posttraumatic stress disorder (CPTSD) diagnosis and whether disturbances in self-organization (DSO) in CPTSD can be differentiated from borderline personality disorder (BPD). How PTSD is defined may matter. The present study used exploratory structural equation modeling (ESEM) to replicate and extend prior work by including two models to examine how PTSD ( ICD-11, DSM-5 ), DSO, and BPD symptoms relate. Participants ( N = 470; 98.1% women; 97.7% Black) were recruited from medical clinics within an urban hospital. PTSD, CPTSD, and BPD were assessed using semi-structured interviews and trauma-related avoidance, aggressive behavior, and anxious attachment were assessed using self-report measures. ESEM models of PTSD, DSO, and BPD symptoms were run. We found a three-factor ESEM model of CPTSD ( ICD-11 PTSD and DSO symptoms) and BPD symptoms best fit the data and found support for discriminant validity between factors across trauma-related avoidance, aggressive behavior, and anxious attachment. For DSM-5 PTSD, a two-factor ESEM model was best-fitting (PTSD and DSO/BPD). The findings demonstrate clear distinguishing and overlapping features of ICD-11 PTSD, CPTSD, and BPD and the necessity to consider the diagnostic structure of PTSD in determining the additive value of CPTSD as a distinct construct. Highlights: Exploratory SEM was used to identify overlap between complex PTSD and BPD. Distinguishing features of ICD-11 complex PTSD and BPD were found in urban sample. There was more overlap between BPD and complex PTSD when using DSM-5 PTSD symptoms. Consideration of the diagnostic structure of PTSD used is critical.